Comparative Effectiveness of Surgical Vs. Conservative Treatment in Managing Acute Achilles Tendon Ruptures - Muhammad Saad Ilyas, Zubair Khalid, Uzair Rashid, Ali Irfan, Muhammad Abubakar, Fahad Nazir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Acute Achilles tendon rupture is a common injury, particularly in active individuals, with significant implications for mobility and quality of life. Objective: To evaluate and compare the functional outcomes, complication rates, and return-to-activity timelines in patients treated surgically versus conservatively for acute Achilles tendon rupture. Methods: This prospective comparative study was conducted at Department of Orthopedics and Spine Surgery,Ghurki Trust Teaching Hospital, Lahore from 20 December 2022 to 10 July 2023. The study included patients aged between 18 and 60 years presenting with a primary, unilateral, acute Achilles tendon rupture confirmed by clinical examination and ultrasound or MRI within 7 days of injury. All participants were counseled regarding both surgical and conservative treatment options, and allocation to either group was based on shared decision-making after explaining potential benefits and risks. A total of 86 patients were enrolled. Patients were divided into two groups: group A (n=44) underwent surgical repair, and group B (n=42) received conservative treatment involving immobilization followed by a functional rehabilitation protocol. Results: The surgical group demonstrated a significantly lower re-rupture rate (2.3% vs. 9.5%, p = 0.04) and higher AOFAS scores at 6 months (91.3 ± 5.2 vs. 88.1 ± 6.4, p = 0.03). Return to activity was faster in the surgical group across all activity levels (mean 14.2 weeks vs. 17.5 weeks, p < 0.001). However, the surgical group experienced higher complication rates, including wound infection (6.8%) and sural nerve irritation (4.5%). Patient satisfaction was slightly higher in the surgical group (91% vs. 83%, p = 0.08), though not statistically significant. Conclusion: It is concluded that surgical treatment offers better functional outcomes and faster recovery, particularly for active individuals, but carries a higher risk of local complications. Conservative management remains a safe and effective option for low-demand patients. Keywords: Rupture, Surgical, Techniques, Tendon, Pain, Treatment